The Influence of Company Strategy, Enterprise Risk Management, Company Size and Leverage On Environmental Performance - Pambudi Raharjo, Tyas; Hasnawati , Hasnawati (Green Publisher Indonesia, 2022)
This study aims to analyze the influence of corporate strategy, enterprise risk management (ERM), company size, and leverage on environmental performance. The object of research chosen is companies incorporated in the primary consumer goods industry, non-primary consumer goods, and health (manufacturing) listed on the IDX in the period 2017 – 2020. The sampling technique used is purposive sampling. The data that meets the criteria for processing amounts to 97 observational data. This study used a multiple linear regression model as an analysis technique and use PLS to process the data. The results of this study found that the ERM has a positive and Leverage has a negative effect on environmental performance while the differentiation strategy, ERM, company size, and leverage do not affect environmental performance.